Tolerance features to uncertainty and students’ viability depending on their gender - L. O. Pelepchuk; N. A. Tsvetkova (Вестник университета)
The study subject is tolerance to uncertainty and viability. The purpose of the work is to determine their level in male and female students and identify intersex distinctions. The methodological tools were: a personality-oriented approach and a testing methods (the McLane uncertainty tolerance test modified by E.N. Osin and the human viability test by E.A. Rylskaya). The sample consisted of 70 boys and 70 girls. The following main results are noted: students have a moderate overall level of tolerance to uncertainty and viability. Boys showed higher results in tolerance to uncertainty and its general level, and girls – in viability. The obtained data are important for assessing the psychological readiness of students to adapt to situations of uncertainty and to be productive in them. The study needs to be continued on a wider sample, taking into account regional specifics. The authors concluded that the complete absence of students with a high level of viability in the sample means that the measures implemented by the institutions of family and education are insufficient.